2014
DOI: 10.1002/bem.21863
|View full text |Cite
|
Sign up to set email alerts
|

Decreased P‐glycoprotein is associated with the inhibitory effects of static magnetic fields and cisplatin on K562 cells

Abstract: In this study, we explored the mechanism of the killing effects of a moderate-intensity static magnetic field (SMF) and cisplatin (DDP) on K562 cells. We analyzed the metabolic activity of cells, the extracellular DDP content, and P-glycoprotein (P-gp) expression after K562 cells were exposed continuously to a uniform 8.8 mT SMF for 8 h, with or without DDP. We found that SMF combined with DDP (10 µg/ml) significantly inhibited the metabolic activity of K562 cells (P < 0.05), while neither DDP nor SMF alone af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Interestingly, these results were in keeping with ABCB1 transcript levels assessed by real-time PCR, performed after 48 h incubation with the investigated compounds. In the past, the impact of ATP-binding cassette transporters such as P-gp in mediating multi-drug resistance in chronic erythromyeloblastoid leukemia cells has been reported [ 36 ]. We found that transcription of the multi-drug resistance ABCB1 gene in K562/DOX cells was about 3-fold higher than that in the parental DOX-sensitive cell line K562.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these results were in keeping with ABCB1 transcript levels assessed by real-time PCR, performed after 48 h incubation with the investigated compounds. In the past, the impact of ATP-binding cassette transporters such as P-gp in mediating multi-drug resistance in chronic erythromyeloblastoid leukemia cells has been reported [ 36 ]. We found that transcription of the multi-drug resistance ABCB1 gene in K562/DOX cells was about 3-fold higher than that in the parental DOX-sensitive cell line K562.…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate SMF therapy increased the sensitivity of ovarian cancer cells, such as A2780 and A2780-CP, to cisplatin depending upon dose and exposure time, via producing small holes and large verrucous structures on the surface of the cell membrane (27,98). The expression of Pglycoprotein is associated with multidrug resistance (MDR) in cancer cells, which is one of the main mechanisms of drug resistance in cancer cells (99). A combination with the SMF (8.8 m T, 12 h) decreased the expression of P-glycoprotein (P-gp) in K562 cancer cells, while adriamycin itself induced an increase (28).…”
Section: Mfs In Combination Therapies In Combination With Chemotherapmentioning
confidence: 99%
“…In the past two decades, analysis results suggest that SMFs can enhance the killing effect of antineoplastic drugs on cancer cells, indicating that SMFs may act synergistically with pharmacological treatment. Previous experiments have shown that combined treatment of 8.8 mT SMF with 10 mg/ml cisplatin (DDP) resulted in the inhibition of metabolic activity, a change in cell cycle distribution and serious damage to deoxyribonucleic acid (DNA) [2]. The application of SMF to human leukemia cells, combined with a mixture of chemotherapy drugs (5-fluorouracil, cisplatin, doxorubicin, and vincristine), enhanced the cytotoxic effects of the drugs in an in vitro cell growth assay1.…”
Section: Introductionmentioning
confidence: 99%